Effect of Surface Treatment with Er;Cr:YSSG, Nd:YAG, and CO(2) Lasers on Repair Shear Bond Strength of a Silorane-based Composite Resin - Alizadeh Oskoee, Parnian (Tabriz University of Medical Sciences, 2013)
Background and aims. The aim of the present study was to compare the effect ofsurface treatment with Er; Cr:YSSG, Nd:YAG, and CO(2) lasers on repair shear bond strength of a silorane-based composite resin. Materials and methods. Sixty eight cylindrical samples of a silorane-based composite resin (Filtek Silorane) were pre-pared and randomly divided into 4 groups as follows: group 1: without surface treatment; groups 2, 3 and 4 with surface treatments using Er; Cr:YSSG, Nd:YAG, and CO(2) lasers, respectively. A positive control group (group 5) was assigned in order to measure cohesive strength. Repair shear bond strength values were measured and data was analyzed using one-way ANOVA and a post hoc Tukey test at a significance level of α=0.05. Results. There were statistically significant differences in repair shear bond strength values between group 2 and other groups (P < 0.05); and between group 1and groups 3and 4 (P < 0.001); however, there were no significant differences be-tween groups 3 and 4 (P = 0.91). Conclusion. The repair shear bond strength of silorane-based composite resin was acceptable by surface treatment with lasers